Kedudukan Omnibus Law Dalam Sistem Hukum Indonesia. Berdasarkan Undang-Undang Nomor 13 Tahun 2022 Tentang Pembentukan Peraturan Perundang-Undangan - Agustian, Muhamad Yosi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
By using the omnibus law method, you can create a rule or law consisting of many subjects or basic materials for a specific purpose and deviate from the standard rules. An Omnibus Law differs from a draft regulation mainly because it covers a lot of subject matter, has many regulated articles, and lastly, because it is more complexParagraphs (1a) and (1b) of Article 64 of Law Number 13 of 2022 on the Formation of Legislation and Factors for Rejection of Omnibus Law due to Regulatory Conflict regulate the position of Omnibus Law. To avoid regulatory conflicts, the Omnibus Law formation process must involve the government and the House of Representatives (DPR) openly and inform the public in advance.